SMART RECOVERY: EDUKASI PENANGANAN CEDERA OLAHRAGA RINGAN BERBASIS DIGITAL BAGI GURU DAN SISWA SMP DI KABUPATEN BANYUMAS - Hidayat, Rohman; Febriani, Ayu Rizky; Kuat Leksono; Duaji Rahadyan Nursantiko; Septiana Dwi Rakhmawati (Jurnal Pengabdian Indonesia (JPI), 2026)
Sports-related minor injuries are common occurrences in school-based physical education activities, yet literacy regarding appropriate first aid management remains limited among teachers and students. This community service program aimed to improve knowledge, skills, and preparedness in managing minor sports injuries through a digital-based educational intervention entitled Smart Recovery. The program was implemented among junior high school (SMP) teachers and students in Banyumas Regency, Indonesia, using a participatory and technology-integrated approach. Activities consisted of program socialization, theoretical and practical training on minor injury management based on the RICE principle (Rest, Ice, Compression, Elevation), and the pilot implementation of the Smart Recovery digital application. Program effectiveness was evaluated using pre-test and post-test assessments, practical skill observations, and user feedback questionnaires. The results demonstrated a substantial improvement in participants’ knowledge, with average scores increasing from 62.4 to 88.6, and 95% of participants successfully performing the RICE procedures correctly after training. Furthermore, 92% of users reported that the digital application facilitated their understanding of injury management, while 87% perceived the platform as user-friendly and applicable for physical education learning. The integration of hands-on training and digital learning media proved effective in enhancing sports injury literacy, digital competence, and safety awareness in school settings. These findings indicate that the Smart Recovery program has strong potential as a sustainable and scalable model for promoting sports safety education within junior high schools. Keywords : minor sports injury; RICE method; digital learning; Smart Recovery; physical education